The effect of pre-irradiation defects on the recombination luminescence in activated crystals K2SO4 - Кoketai, T.; Тagayeva, B.; Тussupbekova, A.; Mussenova, E. (ELSEVIER SCIENCE BV, 2015)
The recombinational luminescence of crystals of K2SO4-Mn2+ and K2SO4-Ni2+ is studied in the article. It is established that impurity ions form the radiation induced centers. The cause of changes of the distribution of lightsum on TSL peaks of a matrix is established. It is proposed that it is related to pre-radiation defeсts in crystals. It is established from this effect that ions of Mn2+ and Ni2+ selectively replace cations in a crystal lattice of potassium sulfate.
Keywords: Potassium sulphate; recombinational luminescence; defeсts